Black stork (Ciconia nigra) in the Belorussian Lakeland in 2001–2014 years - Івановський, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
During 2001–2014 years in the Belorussian Lakeland 27 cases of reproduction of black stork were detected on 10 nesting areas. In the nests with down nestlings in average 3.7±0.2 nestlings were revealed. In the nests with feathered nestlings in average 3.5±0.2 nestlings were registered. Reproduction success (n=9) was 100%. During this period compared with the period of 1991–2000 years the width of ecological niche by the parameter of nesting biotop narrowed from 1,776 to 1,200. The parameter of nesting tree species also narrowed from 5,319 to 2,778. Possible reasons of such event are discussed.